Gerd-Q Score As Outcome Parameter Of Anterior vs. Posterior Peroral Endoscopical Myotomy in Acalasia Patient - Athala Rania Insyira; I Gede Bramantya Surya Mahendra; Ni Komang Ayu Trisnayanti Yasa; Nimas Resti; Nofiana Ayu Risqiana Sari; Catarina Budyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Achalasia is an esophageal motility disorder which is characterized by relaxation failure of the lower esophageal sphincter and absence of distal esophageal peristalsis. The prevalence rate of achalasia is 10 cases per 100,000 population with dysphagia, regurgitation, chest pain, and weight loss as the main clinical manifestations. Target of treatment for achalasia is a decreased resting pressure in the lower esophageal sphincter and this can be achieved using peroral endoscopic myotomy (POEM). POEM can be performed using two therapeutic approaches: anterior and posterior. Complication that often occurs after POEM is Gastroesophageal Reflux Disease (GERD). GERD leads to symptoms and/or structural damage that affects the patient’s quality of life. The GERD questionnaire (GERD-Q) is a sensitive and non-invasive screening tool for diagnosing GERD. Based on the result analysis of this research that was conducted to assess the outcome of anterior and posterior POEM with the GERD-Q score parameter, there was no significant difference in scores between the anterior and posterior approaches.